The Role of DevOps in Mobile Application Development: CI/CD Pipelines for Faster Releases (Information Horizons: American Journal of Library and Information Science Innovation (2993-2777), 2023)
In today’s fast-paced digital landscape, the demand for rapid, reliable, and high-quality mobile application releases has never been greater. This article explores the transformative role of DevOps practices in mobile app development, focusing on the design and implementation of Continuous Integration and Continuous Delivery (CI/CD) pipelines. By integrating automated build, test, and deployment processes, DevOps enables development teams to accelerate release cycles while maintaining rigorous quality and security standards. The article delves into key pipeline components tailored for mobile platforms including version control, automated testing frameworks, artifact management, and deployment automation highlighting best practices and common challenges. Real-world case studies illustrate how leading organizations leverage DevOps to reduce time-to-market, enhance collaboration between development and operations, and deliver seamless user experiences. Ultimately, the article demonstrates that adopting DevOps and CI/CD pipelines is essential for modern mobile development teams striving to stay competitive in an increasingly dynamic marketplace.